The Hierarchy of Hamiltonians for a Restricted Class of Natanzon Potentials - Drigo Filho, Elso [UNESP]; Ricotta, Regina Maria [UNESP] (Sociedade Brasileira de Física, 2001)
The restricted class of Natanzon potentials with two free parameters is studied within the context of Supersymmetric Quantum Mechanics. The hierarchy of Hamiltonians and a general form for the superpotential is presented. The first members of the superfamily are explicitly evaluated.